Diagnostic Value of the Fimbriae Distribution Pattern in Localization of Urinary Tract Infection - Li, Xiao; Zhou, Kaichen; Wang, Jingyu; Guo, Jiahe; Cao, Yang; Ren, Jie; Guan, Tao; Sheng, Wenchao; Zhang, Mingyao; Yao, Zhi; Wang, Quan (Frontiers in Medicine, 2021)
Urinary tract infections (UTIs) are one of the most common infectious diseases. UTIs are mainly caused by uropathogenic Escherichia coli (UPEC), and are either upper or lower according to the infection site. Fimbriae are necessary for UPEC to adhere to the host uroepithelium, and are abundant and diverse in UPEC strains. Although great progress has been made in determining the roles of different types of fimbriae in UPEC colonization, the contributions of multiple fimbriae to site-specific attachment also need to be considered. Therefore, the distribution patterns of 22 fimbrial genes in 90 UPEC strains from patients diagnosed with upper or lower UTIs were analyzed using PCR. The distribution patterns correlated with the infection sites, an XGBoost model with a mean accuracy of 83.33% and a mean area under the curve (AUC) of the receiver operating characteristic (ROC) of 0.92 demonstrated that fimbrial gene distribution patterns could predict the localization of upper and lower UTIs.